O dizer na e sobre a língua de sujeitos descendentes de imigrantes italianos e a fronteira enunciativa - Parcianello, Juciane Ferigolo (2011)
This work aims to study the functioning of discursive memory, language and fronteira enunciativa memory in statements of descendants of Italian immigrants. Such statements were retrieved from texts of interviews with five descendents who live in the city Ivorá, Fourth Colony of Italian immigration. For this research, we firstly considered a few aspects of historiographical discourse that refer to the immigration process in Brazil, with emphasis on Italian immigration, and we also pointed out the main causes and consequences of that event to the economic and cultural field of this country. Secondly, we considered the linguistic policies of the Estado Novo as well as the prohibition imposed on the languages of immigration through the nationalization of education. We analyzed some of decree-laws that were prevalent during this period in order to observe how the state interfered in the functioning of Italian language in immigrant colonies, which resulted from this interference. The third stage of this work is characterized by a theoretical review of authors who deal with issues regarding enunciation. We also examined the functioning of the fronteira linguística in enunciative sequences of descendants of Italian immigrants and how they distribute the languages they speak because they are affected by the place of enunciation. The last part of this work is devoted to analytical exercise, at which we analyzed the functioning of discursive memory, language and fronteira enunciativa memory, from a theoretical description of the Semantics of Enunciation. We observed that descendant of Italian immigrants, at predicating on (Italian and Portuguese) language(s), means, in its enunciation, a (political) conflict by the unequal distribution which makes these languages in place of saying. In certain circumstances at enunciating, this political and historical subject establishes a fronteira enunciativa, which means, by the discursive memory and by the language memory, places where it can and should say in each language (Italian and Portuguese).